The Role of Grants in Infrastructure Development Efforts - Muhammad Arif; Silvia Anjani Nasution (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
One of the functions of the government is to budget for regional expenditures in the form or in the form of subsidies or grants and social support aimed at improving the implementation of government functions, improving services to the community, improving regional management services and general basic services, as well as increasing participation in the implementation of regional development or other related activities. functionally related to the field of supporting the administration of government. Infrastructure is one of the basic needs which is an important factor in improving social, community dynamics and productivity. The purpose of this study was to find out how the role and grant funds in the effort to develop facilities and infrastructure..